Transforming food systems in Kenya for a new era of growth and prosperity: Research-based recommendations for the new government - Breisinger, Clemens; Karugia, Joseph T.; Keenan, Michael; Mbuthia, Juneweenex (International Food Policy Research Institute, 2022)
The new Kenyan government faces a complex domestic and global environment, and it is widely expected to address key food and agricultural challenges with a new set of policies and programs. This policy brief presents key recommendations from a forthcoming book, Food Systems Transformation in Kenya: Lessons from the Past and Policy Options for the Future, which provides research-based “food for thought and action” to support the Kenyan government’s efforts to improve food security.